BAGAIMANA MENINGKATKAN KINERJA KARYAWAN PT. RAJAWALI ASIA BALI? - I Nyoman Resa Adhika; Putu Novia Hapsari Ardianti (Universitas Mahendradatta Denpasar, 2024)
PT. Rajawali Asia Bali is one of the ice cream distributors in Bali. PT. Rajawali Asia Bali implements a target-oriented system, so employees are required to be active in order to win the market. Employees are assets and capital for the company for the short and long term, so it is important for the company to be able to maintain and maintain a quality workforce. A reward system that is fair and guarantees the welfare of all workers is a method that must be considered and implemented by the company. In awarding PT. Rajawali Asia Bali has not distributed rewards evenly. Like rewards in financial form, namely inappropriate bonuses received by several employees who can achieve targets. Based on this background, the author raised the research title The Influence of Reward, Punishment and Organizational Culture on Employee Performance at PT. Balinese Asian Eagle. The total sample taken was 96 employees, using a census method where all employees were used as respondents. Data collection was carried out through observation and questionnaires. The analysis techniques used are multiple linear regression, multiple correlation analysis, multiple determination analysis, F test and t test.